An investigation into the clinical impacts of lowering shunt opening pressure in idiopathic normal pressure hydrocephalus: A case series. (2nd January 2015) - Malem, David N.; Shand Smith, James D.; Toma, Ahmed K.; Sethi, Huma; Kitchen, Neil D.; Watkins, Laurence D.
Abstract: Introduction. Idiopathic normal pressure hydrocephalus (iNPH) is a shunt- reversible syndrome of the elderly. Shunt management is aimed at achieving a balance between clinical improvement and the complications associated with overdrainage. Although clinical improvement occurs at low pressure, these benefits may be negated by the increase in complication rates observed at lower pressures. The addition of gravity-switch devices has been shown to reduce over drainage problems even at a low valve pressure setting. At our centre the Miethke proGAV is used and commonly lowered below 5 cmH2 O to gain further clinical improvement. Object. To determine whether lowering the opening pressure to below 5cmH2 O using the proGAV valve in iNPH patients results in a) improved clinical features; and b) no significant increase in complication rates. Methods. A retrospective case series of iNPH patients was undertaken with 24 patients who had the proGAV shunt system inserted with an initial opening pressure of 5cmH2 O. Exclusion criteria were secondary NPH, shunt system other than proGAV inserted, no valve adjustment to below 5cmH2 O and inadequate follow-up. Outcome measures were clinical improvement (gait, cognition and urinary continence) and complications (subdural haematoma, low-pressure symptoms and valve damage). Results. Patients underwent a total of 29 adjustments to below 5cmH2 O. The mean valve opening pressure after the first adjustment was 2.5cmH2 O and the mean opening pressure after the second adjustment was 1cmH2 O. Overall, outcome after adjustment included 26% no change, 48% improvement and 26% deterioration clinically. One patient (4%) suffered traumatic subdural haematoma that resolved with increasing valve pressure to 20cmH2 O. There was no valve damage or low-pressure symptoms after adjustment. Conclusion. This study found that lowering the opening pressure of the proGAV shunt system to below 5cmH2 O results in clinical improvement and does not significantly increase the complication rate in iNPH patients.